Special Forces : the operator - Dees, Cindy (Dees, Cindy. Mission Medusa., 2019)
Intense training has prepared Special Forces member Rebel McQueen for anything<U+2026>that is, except sexy security specialist Avi Bronson. They are complete opposites, and yet only Rebel and Avi believe in an imminent terrorist attack. Together, they must protect thousands of innocent lives. But who will save Rebel from certain heartache if she dares to succumb to Avi<U+2014>and her most dangerous attraction?